2000
DOI: 10.1002/(sici)1096-8628(20000403)96:2<146::aid-ajmg4>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Familial association between allergic disorders and depression in adult Finnish twins

Abstract: Clinical studies have shown a relationship between allergic disorders and depression, panic disorder, attention deficit/hyperactivity disorder, and social anxiety for a significant subset of patients with these disorders. The nature of the relationship, whether due to shared environmental or biologic vulnerabilities or as a result of the stress of chronic illness, has been less clear. By examining the covariance of atopic disorders and depressive symptoms in a community sample of monozygotic (MZ) and dizygotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
82
1
3

Year Published

2001
2001
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(90 citation statements)
references
References 57 publications
4
82
1
3
Order By: Relevance
“…Our findings, based on data from the Northern Finland 1966 Birth Cohort, provide firm support to the findings of previous studies [13][14][15][16][17][18] concerning an association between depression and atopic disorders. The results of this 31-year prospective follow-up, moreover, suggest that in females the presence of atopic symptoms, verified by skin-prick tests, increase the risk of depression up to 4.7-fold when compared with nonatopic female cohort members.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our findings, based on data from the Northern Finland 1966 Birth Cohort, provide firm support to the findings of previous studies [13][14][15][16][17][18] concerning an association between depression and atopic disorders. The results of this 31-year prospective follow-up, moreover, suggest that in females the presence of atopic symptoms, verified by skin-prick tests, increase the risk of depression up to 4.7-fold when compared with nonatopic female cohort members.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that atopic disorders and depression share a common genetic etiology. 13 Since there is evidence that in women genetic factors play a greater role in the etiology of depression than in men, 58,59 we speculate that even the pathophysiology of the atopy-depression association could have arisen from different origins in females and males. For example, with respect to the serotonin metabolism, Enoch et al 60 have recently established that the 5-HT(2A) promoter polymorphism is associated with affective disorders in women but not in men.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A review of studies on perinatal risk and later health problems suggested that exposure to stress in utero and/or early in life may increase vulnerability to subsequent normative stress and impair functions of the central nervous system (CNS) and hypothalamic-pituitary-adrenal (HPA) axis (Sanchez et al 2001). These changes are hypothesized to elevate the risk for both emotion regulation and physical health problems, particularly related to respiratory function (Wamboldt et al 2000) and cardiovascular reactivity (Sanchez et al 2001). Animal studies show that chronic perinatal stress increases the risk for subsequent problems in physical health, affect and behavior (Ward, 1991).…”
Section: Introductionmentioning
confidence: 99%